Guidelines For Developing Operations According to The Internal Educational Quality Assurance System Modern Educational Institution of Schools in The Sahamit Witthaya Educational Quality Development Center, Mae Ai District, Under the Chiang Mai Primary Educational Service Area Office 3 - Thanunchai, Napichaya; Muenjaem, Samnao; Kosanpipat , Sirimas (Journal of Dhamma for Life, 2025)
ABSTRACT This research aims to study the current situation, expectations, and essential needs for implementing the internal quality assurance system in modern educational institutions at Samit Witthaya School in Mae Ai District, which is under the jurisdiction of the Chiang Mai Primary Educational Service Area Office Zone 3. The study seeks to explore approaches to enhance the operation of the internal quality assurance system to establish and verify operational guidelines for the internal quality assurance system in modern educational institutions at Samit Witthaya School, using a sample group of 86 individuals, including school administrators, teachers, and educational personnel. The research findings indicate that: 1) The expectations and essential needs provide insights into the educational institution's information, particularly regarding the necessary developments, especially in the areas of follow-up and evaluation. 2) The approach to developing the operation of the internal quality assurance system in modern educational institutions must integrate technology and involve participation from all relevant stakeholders. 3) The operational guidelines for the internal quality assurance system in modern educational institutions at Samit Witthaya School consist of components including principles, objectives, operational processes, and conditions for success.